Problems in CSF and Ophthalmic Disease Research - Machiele, Ryan; Frankfort, Benjamin Jay; Killer, Hanspeter Esriel; Fleischman, David (Frontiers in Ophthalmology, 2022)
There has been significant interest and progress in the understanding of cerebrospinal fluid pressure and its relationship to glaucoma and other ophthalmic diseases. However, just as every physiologic fluid pressure fluctuates, cerebrospinal fluid pressure (CSFP) is similarly dynamic. Coupling this with the difficulty in measuring the pressure, there are many difficulties in furthering this field of study. This review highlights some of the difficulties in CSFP research, including fluid compartmentalization, estimation equations, and pressure fluctuation. Keeping these limitations in mind will hopefully improve the quality and context of this burgeoning field.